The possibility of a water market in Brazil - Francis C. Petterini (EconomiA, 2018)
The paper examines the possibility of a water market in Brazil. The US market, probably the oldest and most well-documented one, is initially analyzed. In the American West, over the past 140 years the so-called "water rights" can be sold or rented. However, mainly due to high transaction costs, only recently the trading became regular. Analyzing the Brazilian case, it is clear that the country does not have the problem of water availability that the American West has. On the other hand, the Brazil has a precarious infrastructure. To implement a water market, the first step would be to allow the trade of the grantings of right to the use of water. It is argued that this would be an opportunity to force users to invest in water infrastructure. Thus, a model is built to study the conditions under which the market would lead to a Pareto superior situation.
Keywords: Q25; Q56; R52; 330; Brazilian water law; lei das águas do Brasil; mercado de água; Water market; Water right